Association of ambient air pollutants and birth weight in Ningbo, 2015–2017. (June 2019) - Li, Zhen; Yuan, Xiaoqi; Fu, Jianfei; Zhang, Lingyun; Hong, Lixia; Hu, Lingjie; Liu, Liya
Abstract: Previous studies have suggested a change of birth weight linked with elevated ambient air pollutant concentrations during the pregnancy. However, investigations of the influence of higher pollutant levels on birth weight change are limited. The goal of this study is to evaluate whether the air pollution of Ningbo is associated with birth weight, and which trimester could be a window period for maternal exposure to air pollution. A total of 170, 008 live births were selected in the Ningbo city of Zhejiang, China, from 2015 to 2017. We estimated the association between the decreased birth weight and the increased air pollutant concentrations in the three trimesters and full gestation. The effects of interaction among pollutants were identified using a co-pollutant adjustment model. An interquartile range increases in PM2.5 (10.55 μg/m 3 ), SO2 (4.6 μg/m 3 ), CO (125.59 μg/m 3 ), and O3 (14.54 μg/m 3 ) concentrations during the entire gestation were associated with 3.65 g (95% confidence interval: −6.02 g, −1.29 g), 5.02 g (−6.89 g, −3.14 g), 2.64 g (−4.65 g, −0.63 g) and 2.9 g (−4.8 g, 1 g) decreases, respectively, in birth weight. With each interquartile range increment in NO2 concentration was associated with an 8.05 g (6.24 g, 9.85 g) increase in birth weight. In the first trimester, only the PM2.5 exposure seemed to be associated with the greatest decline in birth weight. After adjustment for co-pollutant, both PM2.5 and SO2 were still associated with birth weight, except for CO for O3 adjustment, O3 for SO2 adjustment, and O3 for NO2 adjustment. Maternal exposure to air pollution may be associated with a decrease of birth weight, but the contribution of various pollutants is necessary to verify by future research. Graphical abstract: Image 1 Highlights: The association between air pollution of Ningbo, China, and birth weight is evaluated using a co-pollutant adjustment model. A large number of subjects (170008 births) are included in this study. Air pollutants including PM2.5, SO2, CO, and O3 are analysed in this paper. Abstract : Main Findings : During the entire gestation, an increase of PM2.5, SO2, CO, and O3 is inversely associated with decrease in birth weight, and the level of NO2 is positively linked with birth weight.